Diminution of Active Power Loss by Communal Expressive Optimization Algorithm - Lenin Kanagasabai (Journal of Telematics and Informatics, 2017)
Human society is a multifarious collection which is more effectual than other animal groups. Consequently, if one algorithm imitates the human society, then the efficiency may be healthier than other swarm intelligent algorithms which are stimulated by other animal groups. In this paper Communal Expressive (CE) Optimization Algorithm has been utilized to solve reactive power problem. The key feature of solving Optimal Reactive Power Problem is to reduce the real power loss and to maintain the voltage profile within the specified limits. The proposed Communal Expressive (CE) Optimization Algorithm has been authenticated, by applying it in standard IEEE 118 & practical 191 bus test systems. The results have been compared to other standard methods and the projected algorithm converges to finest solution.